2021
DOI: 10.1055/a-1711-6097
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt-Catalyzed Glaser-type Homocoupling Reaction

Abstract: A highly efficient cobalt-catalyzed homocoupling of terminal alkynes with di-tert-butyldiaziridinone as the oxidant has been developed. The protocol tolerates a wide array of terminal alkynes, both activated and unactivated alkynes, to afford their corresponding conjugated 1,3-diynes. The mild reaction conditions further allow late-stage homocoupling of alkynes derived from complex natural products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Since the pioneering work by Glaser in 1869 [ 30 ], Glaser coupling and its modifications have become one of the most widely utilized and powerful strategies for the synthesis of diverse 1,3-dialkynes [ 31 , 32 , 33 , 34 ]. Numerous metal catalytic systems such as palladium [ 35 , 36 ], cobalt [ 37 , 38 ], ruthenium [ 39 ], and gold, etc., [ 40 , 41 , 42 ] have been studied on this reaction. However, most of their wide applications are limited because of their higher price or instability in air.…”
Section: Introductionmentioning
confidence: 99%
“…Since the pioneering work by Glaser in 1869 [ 30 ], Glaser coupling and its modifications have become one of the most widely utilized and powerful strategies for the synthesis of diverse 1,3-dialkynes [ 31 , 32 , 33 , 34 ]. Numerous metal catalytic systems such as palladium [ 35 , 36 ], cobalt [ 37 , 38 ], ruthenium [ 39 ], and gold, etc., [ 40 , 41 , 42 ] have been studied on this reaction. However, most of their wide applications are limited because of their higher price or instability in air.…”
Section: Introductionmentioning
confidence: 99%
“…While the majority of these reports employ a copper complex as a catalyst, some other earth abundant metal complexes have also shown their potential on promoting Glaser–Hay homocoupling reactions. Thus, Hilt has reported the CoBr 2 ‐catalysed coupling of terminal alkynes using nitrobenzene as a stoichiometric oxidant under reductive conditions, [8] and more recently Ye has described the use of Co(salen) complexes (salen= N,N’ ‐ethylenebis(salicylimine)) to catalyse these reactions employing di‐ tert ‐butyldiaziridinone [9] …”
Section: Introductionmentioning
confidence: 99%
“…Thus, Hilt has reported the CoBr 2 -catalysed coupling of terminal alkynes using nitrobenzene as a stoichiometric oxidant under reductive conditions, [8] and more recently Ye has described the use of Co(salen) complexes (salen = N,N'-ethylenebis(salicylimine)) to catalyse these reactions employing di-tert-butyldiaziridinone. [9] Within manganese chemistry, seminal work by Cahiez has shown that mixed-metal salts such as MnCl 2 • 2 LiCl can catalyse homocoupling of Grignard reagents, including alkynyl-substituted RMgX, using oxygen as oxidant. [10] More recently, Taillefer has also demonstrated that in situ generated Li-aryls and Liacetylides can undergo homocoupling in the presence of air using catalytic amounts of MnCl 2 .…”
Section: Introductionmentioning
confidence: 99%